Análise de risco de ruptura de barragens: estudo de caso de seis barragens na Ilha de Santiago em Cabo Verde-África. - Fernandes, Manuel Moreira (2020)
Cape Verde is part of the group of countries in the world with less water resources. The construction of dams in Cape Verde is a recent fact, the first dam being built in 2006, still in the absence of legislation on dam safety. The lack of experience in the design of dams by national engineering, forced the government to hire international consulting companies for its elaboration. Parallel to this situation, the occurrence of accidents and incidents with dams in Brazil and other countries in the world, is not a mere hypothesis based on a remote past. It is a fact that requires a short-term solution. These accidents in Brazil and other countries, in general, are associated with the way in which dam safety management is handled. Furthermore, the risks associated with the rupture of dams, resulting in the possibility of loss of human life and the generation of enormous material, economic, social and environmental losses, implies the need to define a previous regulatory framework in which countless must be considered. factors linked to the quality of the projects, the safety requirements of the work, the observation and inspection of the execution of the works, and the operational management of the dams. Thus, this work presents a proposal to analyze the risk of rupture of six dams on the Island of Santiago in Cape Verde with a case study of the dams of Faveta, Figueira Gorda, Flamengos, Poilão, Salineiro and Saquinho. The presentation of a study on the emergency action plan (PAE) in the valley downstream of these dams and their respective consequences due to the simulation of an eventual hypothetical rupture of the dams will also be materialized, using the QGIS (geoprocessing), HEC-HMS (rupture hydrograph at Dam Break) and HEC-RAS (2D breakout simulation) programs. According to ANA Resolution No. 136 (2017), the PAE is required for Class A and B dams, and must be prepared for new dams, before the first filling begins, from when it should be available for use. Therefore, the six dams under study will also be classified, in terms of Risk Potential (PR), Risk Criterion (CRI) and in terms of Potential Associated Damage (DPA), based on CNRH of 2012 and Law No. 12,334 of 20 of September 2010, which establishes the National Dam Safety Policy in Brazil - PNSB. Finally, based on extensive research of legislation on dam safety management in several countries and an analysis of the current state of Cape Verde related to the attribution of competencies in terms of water resource management, management and construction of hydraulic infrastructures and legislation on water management. dam safety, a model of the dam safety management system was elaborated, perfectly adapted to the conditions and reality of these islands, with participation not only from existing public authorities and institutions, but also from private authorities, in line with the best international practices on this matter.